The synthesis and characterization of cycloalkoxy-linear phosphazenes - Ozturk, AI; Aslan, F; Cil, E; Arslan, M; Kiliç, A (Taylor & Francis Ltd, 2003)
The reactions of N-dichlorophosphoryl-P-trichlorophosphazene, Cl3P=N-P(O)Cl-2 with the sodium salts of cyclopentanol, cyclohexanol, 4-methylcyclohexanol, 3-methylcyclohexanol, 3-methylcyclopentanol are discussed. Pentacycloalkoxy-substituted phosphazenes were obtained from cyclopentanol, 4-methylcyclohexanol, 3-methylcyclohexanol, 3-methylcyclopentanol. Tetrasubstituted derivative also was obtained from cyclohexanol at the same conditions. The structure of products was defined by IR, H-1, C-13, P-31 NMR, and mass spectroscopy.
Keywords: alcoholysis; alkoxyphosphazenes; cycloalkoxyphosphazenes; linear phosphazenes; monophosphazenes